TourGo: gamified augmented reality tour / Abdul Hakim Mohd Noor ... [et al.] - Mohd Noor, Abdul Hakim; Rasli, Muhammad Asmu'i; Mohd Alkhadzari, Muhammad Amin Saifuddin; Sh Abdul Nasir, Sheikh Mohd Firdaus; Ahmad Nazri, Mohammad Afif (Universiti Teknologi MARA, Kedah, 2019)
Planning for vacation or travelling to other places can be a hassle when you need to figure out the answer for questions such as; which airlines should you choose? how much should you spend? where should you stay? and many more things to think of. Well, your next vacation might not be that hard. Just leave it to TourGO app! Your best buddy for travelling. Just tell it; where? when? and how much you rather spend and it will automatically plan your best arrangement. The best part is you will be able to play with amazing Augmented Reality (AR) world. Historical places will come to life and you can interact with it. You also can opt for missions and get reward at the end of the day. This app also will help local business to promote their business in a unique and creative way. Penang alone had attracted more than 6 million tourists in 2017 and the rising trend of backpackers travel among millennials increase the demand of curated personalized experiences.